Eine Fallstudie über die regionalen Unterschiede der ungarischen Schülerleistungen - HEGEDŰS, ROLAND; SEBESTYÉN, KRISZTINA (Glottodidactica, 2019)
The sociocultural and socioeconomic background of pupils is a determinant for their learning process and it has an effect on their learning success and on how easily pupils are able to master the requirements set by school curricula and how they perform on different measuring tasks. This is the reason why we compare in our paper the reading and mathematics results of the National Competence Measurement 2013 with the English and German language results of the secondary school-leaving exams in foreign languages regarding the same pupils. We analyse the data using the SPSS program and we present the results using the MapInfo program. We examine the effects of pupils’ social background, the interactions of different subjects and their regional projections as well. The pupils’ achievements show the same pattern as the development patterns of different geographical areas in Hungary.